Pelatihan Manajemen Keuangan dan Penguatan Kelembagaan Kelompok Ternak - Salehawati, Nurul; Dewi, Meita Puspa; Faozi, Imam; Rozaq, Abdul; Jazuli, Ahmad (PASAI : Jurnal Pengabdian kepada Masyarakat, 2022)
This activity aims to provide training and understanding to livestock groups, so thet can record financial adminitrastion books in accordance with financial accounting standards and institusional reinforcement. This activity was held in two places, namely The Bendosari Livestock Group and The Plosokerep Livestock Grup. In this training, the methods used are observation of discussions with livestock groups about what activities have been carried out in financial recording and institutional strengthening of groups, presentation of material by means of presentations and video playback, the practice of manual financial recording, and use of the Android SME-Financial Accounting Application. The results of this training activity are: (1) socialization activities for institutional strengthening; and the practice of manual financial recording and using applications smoothly, (2) Having the awareness that each group member has a role in strengthening group institutions, (3) Having awareness of the importance of recording every financial transaction and documenting financial transaction notes, (4) Manual recording can be done either by hand or with the SME-Finance Accounting application, and (5) Understand the importance of keeping personal and business transactions separate